Advances in using biomaterials for repairing thin endometrium - Li, Huizhen; Hu, Feihong; Xie, Fuchen; Chen, Xuedong; Wu, Honglian (Frontiers in Bioengineering and Biotechnology, 2025)
Thin endometrium is one of the main factors leading to infertility and miscarriage. The development of biomaterial technology and its clinical applications have shown good effects in promoting endometrial regeneration, improving blood flow, and enhancing cell adhesion, offering new hope for boosting fertility in patients. Therefore, this article aims to review the pathological mechanisms of thin endometrium, existing treatment methods, and research progress of biomaterials in this field, analyze the effects of different types of biomaterials on thin endometrium, and explore their potential and challenges in clinical applications, providing references for future research directions.